Silver Nanoparticles as Drug Delivery System in Combating Infections and Cancer - Ardhendu Kumar Mandal (Challenges and Advances in Pharmaceutical Research Vol. 4, 2022)
Chemotherapy remains a serious difficulty for delivering medications to precise sites of interest against numerous life-threatening infectious diseases, despite advances in medical and pharmaceutical sciences. The majority of medications have a significant toxicity, which causes a variety of side effects and lowers quality of life. Inadequate therapeutic index, limited drug absorption, the development of multiple drug resistance, and undesirable systemic side effects have all been linked to the use of conventional microbicidal agents to treat infections. Due to their ultra small controlled sizes, high surface area, and improved reactivity with active functional structures, antimicrobial silver nanoparticles (AgNPs) have emerged as a potent and efficient agent against infection. AgNPs, after exposure, adhere to cells, penetrate inside the cells, and generate reactive oxygen species (ROS) producing oxidative stress, protein dysfunction, and modification of signal transduction pathways, and damage membranes and deoxyribonucleic acids (DNAs), leading to cellular damages. The surface-ligand coating of AgNPs-incorporated drug as drug delivery vehicle enlightens their sustained drug release with reduced side effects when administered into the body. This review focuses mainly the synthesis, surface-functionalization, mechanism of actions, biomedical applications, therapeutic efficacies, toxicity, biodistribution and elimination of the AgNPs as potential nanomedicinal drug delivery system for targeted therapy against infections and cancer.